Identifying and evaluating the effective parameters in prioritization of urban roadway bridges for maintenance operations. Issue 1 (1st January 2016) - Amini, Amin; Nikraz, Navid; Fathizadeh, Ali
Abstract: Bridges are considered one of the most important traffic arteries, particularly in metropolises. In accordance with big cities traffic, severe structural damages, or damages caused by the destruction of a roadway bridge, have harmful effects on metropolis management and make appropriate repair operations very difficult. Different bridge management and maintenance systems in various countries have included efforts to resolve these problems. Encountering with the limitations in funds allocated to the maintenance operation and facing various deteriorating in the current urban bridge conditions, we need a proper and effective model to prioritize bridges for repairing and maintenance. An appropriate model for this prioritizing needs a proper database and a supportive decision-making system to process the data, which is based on several parameters. These parameters should not be such little that raise the prioritizing errors and should not be such numerous that encounter analysis process with complexity. In this paper, the parameters of prioritizing the urban roadway bridges to repair and maintenance operation are identified and classified through investigation of codes, regulations, guidelines and applied research carried out in various countries; then, through analysing the experts' judgements using the classical statistical tests, a comprehensive evaluation and ranking of these parameters is presented.